(untitled) (Acta Polytechnica CTU Proceedings, 2016)
The article describes the planned modernization of railway stations in Ceská Lípa and Karlovy Vary, their scope and financing. The emphasis is laid on the expected co-financing of these projects from European structural and investment funds planned for the years 2016-2020. It is case of the operational program Transport - OPD2. The study compares the two projects from many aspects, in particular from the economic and structural-urban planning points of view.